Profil Kepatuhan dan Hubungan Pemberian Allopurinol dengan Perubahan Kadar Asam Urat pada Pasien di Puskesmas Bandar Khalifah, Percut Sei Tuan - Salmah Handayani Lubis; Fenny Hasanah; Desy Natalia Siahaan; Eka Ayu Lestari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hyperuricemia is a metabolic disorder that may lead to gout arthritis and complications if not optimally managed. Allopurinol is the first-line therapy, but treatment success is strongly influenced by patient adherence and achievement of target uric acid levels. Objective: This study aimed to analyze the adherence profile and the correlation of allopurinol administration with changes in uric acid levels among patients at Bandar Khalifah Primary Health Center. Methods: A prospective descriptive observational design was conducted on 55 patients receiving allopurinol therapy from February to April 2025. Data were collected from medical records, laboratory results, and the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire. Results: Most patients (96%) experienced a reduction in uric acid levels, but the mean post-therapy level (6.46 mg/dL) remained above the target of <6 mg/dL. Mild adverse effects were reported in 14.5% of patients, while 85.5% had no complaints. High adherence was found in 54.5% of patients, moderate adherence in 30.9%, and low adherence in 14.6%. Conclusion: Allopurinol therapy demonstrated good clinical effectiveness and safety; however, dose optimization and regular monitoring are required, particularly in patients with low adherence or comorbidities, to achieve the recommended uric acid target.